Self-Management Pada Lansia Penderita Hipertensi Di Desa Tanak Beak Wilayah Kerja Puskesmas Narmada: Self-Management for Elderly People Suffering from Hypertension in Tanak Beak Village, Narmada Health Center Working Area - Heni, Baik Heni Rispawati; Ernawati; Supriyadi; Riskawaty, Heny Marlina (Chakra Brahmanda Lentera Institute, 2023)
Hypertension is also known as the